Optimal adjustment od FE model of concrete slab exposed to impact loading - Jindra, Daniel; Hradil, Petr; Kala, Jiří (EDP Sciences, 2020)
Numerical approach using FEM has been used to describe the behaviour of concrete slab exposed to impact loading. 3D parametrical numerical model has been created, and the influence of various parameters values on model response is being investigated. The analyses have been conducted using explicit numerical solver of commercially available software LS-Dyna. The optimal adjustment of the model has been determined.

Numerical approach using FEM has been used to describe the behaviour of concrete slab exposed to impact loading. 3D parametrical numerical model has been created, and the influence of various parameters values on model response is being investigated. The analyses have been conducted using explicit numerical solver of commercially available software LS-Dyna. The optimal adjustment of the model has been determined.
Optimal adjustment od FE model of concrete slab exposed to impact loading
Keywords: Optimal; adjustment; FE; model; concrete; slab; exposed; impact; loading; Optimal; adjustment; FE; model; concrete; slab; exposed; impact; loading